2016
DOI: 10.2967/jnumed.115.170738
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Imaging and Therapy: Potential Role of Nanoparticles

Abstract: Over the last 2 decades, the use of nanoparticle imaging has been investigated extensively for both diagnosis and therapy of prostate cancer. This review discusses the various classes of nanoparticles currently in clinical use or at the advanced preclinical stage. In particular, we focus on the unique properties of nanoparticles, as a group, that make them suitable for imaging and therapy. The characteristics of each nanoparticle are detailed. Iron oxide nanoparticles, extensively used for MRI of prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Various applications are envisioned for these materials including stand-alone biosensors, light harvesting and biocomputing devices, along with theranostics, the latter of which provides perhaps one of the more illustrative concepts reflecting the longer-term possibilities. For example, within a putative oncological theranostic device, the NP could provide MRI or other in vivo contrast while simultaneously acting as a central scaffold to host biologicals such as antibodies for tumor targeting, peptides for facilitated cellular uptake, and poorly soluble chemotherapeutics for specified delivery. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various applications are envisioned for these materials including stand-alone biosensors, light harvesting and biocomputing devices, along with theranostics, the latter of which provides perhaps one of the more illustrative concepts reflecting the longer-term possibilities. For example, within a putative oncological theranostic device, the NP could provide MRI or other in vivo contrast while simultaneously acting as a central scaffold to host biologicals such as antibodies for tumor targeting, peptides for facilitated cellular uptake, and poorly soluble chemotherapeutics for specified delivery. , …”
mentioning
confidence: 99%
“…For example, within a putative oncological theranostic device, the NP could provide MRI or other in vivo contrast while simultaneously acting as a central scaffold to host biologicals such as antibodies for tumor targeting, peptides for facilitated cellular uptake, and poorly soluble chemotherapeutics for specified delivery. 11,12 Some types of biologically functionalized NPs, such as antibody-decorated gold colloids, have now been in use for several decades, 7 however, it is only recently that the promise and the complexity of such hybrid materials have started to be fully realized. The latter is exemplified by the many requirements surrounding the optimal assembly of these composite materials including: (i) NP synthesis, (ii) surface functionalization, and (iii) bioconjugation.…”
mentioning
confidence: 99%
“…The term nanomaterials refer to structures of nanometric size, generally inferior to 100 nm, which may have a biologic origin, as in the case of lipid-based systems, lactic acid or dextran, as well as predominant inorganic characteristics, as in the case of polymers, silica, metals or carbon lattices [40]. One of nanomaterials' most fascinating properties lies in the possibility of functionalizing their wide surface with specific ligands, thus generating nanosized targeted vehicles of both imaging and therapeutic agents [96]. Figure 5 illustrates the variety of nanomaterials suitable for theranostics.…”
Section: Theranostic Applications Of Radioconjugated Nanomaterials Inmentioning
confidence: 99%
“…Regarding MRI/MRT used in PCa related NP settings the number of publications is constantly increasing [104,339,340,341,342,343,344]. Jin et al, for example, evaluated MRI-guided focal NP-based (porphysomes) photothermal therapy (see below) in an orthotropic PCa mouse model, and concluded that it might be an effective and safe technique to treat PCa, with a low risk of progression of disease [343].…”
Section: Multimodal Imaging Options For Prostate and Breast Cancermentioning
confidence: 99%